Efficiency of Tourism Activities in Ukraine: A Regional Comparison - HORBAN, Halina; PETROVSKA, Iryna; KUCHER, Anatolii; DIUK, Anna (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020DO - 10.14505//jemt.v11.4(44).11, 2020)
The purpose of the research is to evaluate the efficiency of functioning of tourism entities in the regions of Ukraine using the method of analysis of the functioning environment. It was found that in terms of cost effectiveness, the activities of tour operators in the cities of Kyiv, Lviv, Volyn, and Chernihiv regions were technically effective in 2018, and in other regions ineffective. At the same time, the travel agents of Kyiv, Cherkasy, Lviv and Poltava regions took the leading positions in terms of technical efficiency of operating expenses. According to the results of evaluating the technical effectiveness of the tour operators', tour agents' and subjects' of excursion activity total costs, the analyzed regions are grouped into three groups: (i) entities that form the operating environment – the regions whose positions form the line of technical efficiency, that is, technically effective (Kyiv, Kherson, Volyn, and Chernihiv regions); (ii) the entities whose tourism activities affect the operating environment are the positions of the regions between the technical efficiency line and its projection (Ivano-Frankivsk, Kyiv, Lviv and Odesa regions); (iii) entities whose tourism activities do not affect the environment and depend on the status of such activities in other regions (Vinnytsia, Transcarpathian, Rivne and Cherkasy regions). The results of the study can be used in planning measures to improve the technical efficiency of the tourism business in the regions of Ukraine.